Ecritures digitales Digital Writing, Digital Scriptures - Clivaz, Claire (Digital Biblical Studies, 2019)
Ecritures digitales aims to demonstrate how digital writing, as new technology, contributes to the emergence of a reconfigured relationship between the human body and the machines, and how this transition influences the Jewish-Christian textual corpus referred to as "the Scriptures". Ecritures digitales souhaite démontrer de quelle manière l'écriture digitale, en tant que nouvelle technologie, contribue à l'émergence d'une relation innovante entre le corps humain et les machines, et influence le corpus textuel judéo-chrétien désigné comme «les Ecritures». Readership: Tout lecteur ou lectrice intéressé/e à l'analyse des transformations provoquées par l'émergence de l'écriture numérique et la digitalisation du corpus textuel biblique. All interested in the cultural transformations prompted by the emergence of digital writings and the digitalization of the Biblical textual corpus.